Case 3799: Anas boschas domestica Brünnich, 1764 (Aves, Anatidae) (currently Anas platyrhynchos domestica) and Anas anser domesticus Brünnich, 1764 (Aves, Anatidae) (currently Anser anser domesticus): proposed conservation of subspecific names in conformance with prevailing usage, and resolution of type species for the genus Anser Brisson, 1760 by reversing priority of Anas adunca Linnaeus, 1758 in favour of Anas boschas domestica Brünnich, 1764 and further by either (i) recognising authorship by Brisson (1760) of Anser domesticus or (ii) deeming Brünnich’s two names not to be primary homonyms and deeming Anas anser Linnaeus, 1758 as type species of Anser Brisson, 1760 - Donegan, Thomas M (Bulletin of Zoological Nomenclature)
Noticed in BZN 76 (30 Aug 2019): 98.